Role of MSC‐derived small extracellular vesicles in tissue repair and regeneration - Aguiar Koga, Bruna Andrade; Fernandes, Letícia Alves; Fratini, Paula; Sogayar, Mari Cleide; Carreira, Ana Claudia Oliveira (Frontiers in Cell and Developmental Biology, 2023)
Mesenchymal stem cells (MSCs) are crucial for tissue homeostasis and repair, secreting vesicles/exosomes to the extracellular environment. Isolated exosomes were shown to affect angiogenesis, immunomodulation, and tissue regeneration. Numerous efforts have been dedicated to probing into the mechanism of action of these exosomes and assessing their safety since their final aim is a therapeutic application in the clinic. The major advantage of these vesicles, relative to MSCs, is their low or inexistent immunogenicity, prompting their use as drug delivery or therapeutic agents, as well as in vaccination or as biomarkers for wound healing, different cancer types, and inflammatory processes occurring in the nervous and cardiovascular systems. MSCs are easily maintained in vitro, continuously releasing exosomes and soluble peptide factors, in addition to proliferating and differentiating to replace the damaged tissue, however, they may also cause tumor modulation, in addition to accumulating and obstructing small vessels present in organs. On the other hand, MSCs-derived exosomes display no vascular obstruction effects or apparent adverse effects, their nanosize ensure their passage through the blood-brain barrier demonstrating no cytotoxic or immunogenic effects. Several pre-clinical tests have been conducted with exosomes obtained from diverse sources to address their biology, molecular content, signaling pathways, and mechanisms of action. Application of exosome use in human therapies has recently become a reality, with clinical trials being conducted with them from diverse sources to treat Alzheimer's, retina degeneration, and Covid-19 patients. Here, we describe and compare the different exosome isolation methods and therapeutic applications regarding the tissue repair and regeneration process and present the latest clinical trials reports with their newly developed therapeutic protocols employing these vesicles.